Neutrophils Friend or foe in Filariasis? - Ajendra, Jesuthas (Parasite Immunology, 2022)
Abstract Infection with the filarial nematodes that cause diseases such as lymphatic filariasis and onchocerciasis represent major public health challenges. With millions of people at risk of infection, new strategies for treatment or prevention are urgently needed. More complete understanding of the host immune system's ability to control and eliminate the infection is an important step towards fighting these debilitating infectious diseases. Neutrophils are innate immune cells that are rapidly recruited to inflamed or infected tissues and while considered primarily anti‐microbial, there is increasing recognition of their role in helminth infections. Filarial nematodes present a unique situation, as many species harbour the bacterial endosymbiont, Wolbachia. The unexpected involvement of neutrophils during filarial infections has been revealed both in human diseases and animal studies, with strong evidence for recruitment by Wolbachia. This present review will introduce the different human filarial diseases and discuss neutrophil involvement in both protective immune responses, but also in the exacerbation of pathology. Additionally, we will highlight the contributions of the murine model of filariasis, Litomosoides sigmodontis. While several studies have revealed the importance of neutrophils in these parasite infections, we will also draw attention to many questions that remain to be answered.